Classification of Gambling in Positive Law and Islamic Law: A Study of the Entertainment Elements of Claw Doll Games - Fitri, Khatimul; Fauzi, Muhammad; Mursal, Mursal (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
The development of gambling presents complexities within both positive law and Islamic law. In Indonesian positive law, gambling is strictly regulated to protect society, whereas in Islamic law, gambling is deemed haram due to its moral and economic harm to individuals and society. This study examines the claw machine game, which is often considered entertainment but raises questions about its legal status as gambling. This research employs a normative legal method with a comparative analysis to contrast the perspectives of positive law and Islamic law regarding the claw machine game. The results show that, under positive law, there is a classification for determining gambling, and this game is considered entertainment. In contrast, Islamic law does not classify entertainment as a factor in evaluating this game, and it is considered a form of gambling. [Perkembangan judi menghadapi kompleksitas dalam hukum positif dan hukum Islam. Dalam hukum positif Indonesia, perjudian diatur ketat untuk melindungi masyarakat, serta dalam hukum Islam, perjudian dianggap haram karena merugikan individu dan masyarakat secara moral dan ekonomi. Penelitian ini mengkaji permainan capit boneka, yang sering dianggap sebagai hiburan, namun dipertanyakan status hukumnya sebagai perjudian. Penelitian ini menggunakan metode hukum normatif dengan analisis komparatif untuk membandingkan perspektif hukum positif dan hukum Islam mengenai permainan capit boneka. Hasil menunjukkan bahwa dalam hukum positif terdapat klasifikasi dalam menentkan perjudian dan permainan ini dianggap sebagai hiburan. Sedangkan hukum Islam tidak mengklasifikassikan hiburan dalam menilai permainan ini dan dianggap sebagai bentuk perjudian].